A Contrastive Analysis of Beauty Adjectives in Japanese and Indonesian: Strategies for Developing Teaching Materials Based on Linguistic Intervention - Ika Hervina Widyaningtyas (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the systemic differences between Japanese beauty adjectives (utsukushii, kirei, suteki) and Indonesian ones (indah, cantik, bagus) and to formulate strategies for developing teaching materials based on contrastive findings. The research employs a qualitative descriptive approach with syntactic and semantic contrastive analysis techniques. Data were drawn from Haruki Murakami's novel Noruwei no Mori and contemporary Indonesian novels. The results show three main findings: (1) there are significant differences in contextual meaning distribution, although syntactic functions are relatively similar; (2) kirei has semantic ambiguity (clean vs. beautiful) not found in cantik; (3) suteki is more subjective and evaluative compared to bagus. Based on these findings, this study proposes a contrastive-based framework for teaching material development focusing on addressing specific difficulties of Indonesian students. The pedagogical implications can serve as a reference for Japanese language teachers in developing more effective and contextual learning materials.